Association of Hemolytic Activity of Pseudomonas entomophila, a Versatile Soil Bacterium, with Cyclic Lipopeptide Production - Vallet-Gely, Isabelle (American Society for Microbiology (ASM), 2010)
Pseudomonas entomophila is an entomopathogenic bacterium that is able to infect and kill Drosophila melanogaster upon ingestion. Its genome sequence suggests that it is a versatile soil bacterium closely related to Pseudomonas putida. The GacS/GacA two-component system plays a key role in P. entomophila pathogenicity, controlling many putative virulence factors and AprA, a secreted protease important to escape the fly immune response. P. entomophila secretes a strong diffusible hemolytic activity. Here, we showed that this activity is linked to the production of a new cyclic lipopeptide containing 14 amino acids and a 3-C(10)OH fatty acid that we called entolysin. Three nonribosomal peptide synthetases (EtlA, EtlB, EtlC) were identified as responsible for entolysin biosynthesis. Two additional components (EtlR, MacAB) are necessary for its production and secretion. The P. entomophila GacS/GacA two-component system regulates entolysin production, and we demonstrated that its functioning requires two small RNAs and two RsmA-like proteins. Finally, entolysin is required for swarming motility, as described for other lipopeptides, but it does not participate in the virulence of P. entomophila for Drosophila. While investigating the physiological role of entolysin, we also uncovered new phenotypes associated with P. entomophila, including strong biocontrol abilities.